Electrical connectors for surface solderless mounting - Yefimenko, A. A. (Technology and design in electronic equipment, 2012)
The article describes the features of development, possibilities of manufacture and application of electrical connectors for surface mounting with flexible printed cables and elastomer liners. With regard to characteristics, manufacturability and, especially, mounting technological effectiveness, they can rival connectors with digital metal contacts.